(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2024)
This article examines the influence of social media on language usage and individual identity. In today’s interconnected world, social media platforms like Facebook, Twitter, and Instagram have transformed the ways people communicate, creating new linguistic phenomena and shaping personal and group identities. The study explores how social media affects language variation, the emergence of new expressions, and its broader social and cultural impact on identity formation.